PENGARUH PENGELOLAAN BENGKEL TERHADAP MOTIVASI BELAJAR DAN KETERAMPILAN PRAKTIK SISWA SMKN BULO - Muhammad Hasbi; Purnamawati; Abdul Muis (Universitas Negeri Makassar, 2023)
This study aims to determine: 1) The effect of workshop management on learning motivation, 2) The effect of workshop management on practical skills, and 3) The effect of workshop management on learning motivation and practical skills of students at SMKN Bulo. The variable in this study is workshop management as the independent variable, with the dependent variable being students' motivation to learn practical skills. Data collection techniques used two ways, namely questionnaires and documentation. The sample in this study was class XII students with a total of 31 students. Data analysis techniques using the t test. The results of the study show that: (1) The coefficient of determination R Square is 0.172 which implies that the effect of workshop management on learning motivation is 17.2. (2) The coefficient of determination R Square is 0.156 which implies that the effect of workshop management on practical skills is 15.6%. Distribution t table obtained 2.048. So by looking at the significance value and comparing between t table and t count, we get a significance of 0.028 <0.05 and t count > from t table, namely 4.133 > 2.01174. The hypothesis is accepted. (3) The results of the F test (simultaneous) show that the significance value of the influence of workshop management on learning motivation and practical skills is 0.006 <0.05 and the F count > F table is 6.259 > 2.95. The hypothesis is accepted, there is an influence of workshop management on learning motivation and practical skills simultaneously.